The incidence of first stroke in and around pregnancy: A population-based cohort study from Sweden - Ban, Lu; Abdul Sultan, Alyshah; Stephansson, Olof; Tata, Laila J.; Sprigg, Nikola; Nelson-Piercy, Catherine; Bath, Philip M.W.; Ludvigsson, Jonas F. (SAGE, 2017)
Introduction: Research has suggested that delivery is associated with an increased risk of stroke in women; however, there is a lack of contemporary estimates on the incidence of stroke in and after pregnancy compared with the baseline risk in women of childbearing age in Sweden.